022 Hospice-based multi-disciplinary clinic for end-stage renal failure improves quality of care and reduces hospital admission. (1st October 2013) - Wilderspin, Nicola; Turner, Marian; Ferring, Martin; Garside, Jenny; Blaine, Felix; Westwood, Debbie
Abstract : Background/context: Patients opting for conservative management of end-stage renal failure in South Worcestershire frequently died in hospital and struggled to attend acute hospital outpatient appointments. Aims: To improve quality of life through a new hospice-based model of care for conservative management of end-stage renal failure, and provide opportunities for advanced care planning and increased choice in end of life care. Approach: Patients and carers attend a flexible afternoon day hospice 'clinic' which begins with lunch and offers assessments with: An acute hospital nephrologist to proactively manage renal complications such as anaemia and fluid balance. A palliative care CNS/consultant for symptom control, carer assessment and advanced care planning. Complementary therapies and informal chaplaincy support are also provided. Details of advance care plans are communicated to primary and secondary care, and inclusion on GP end of life care registers recommended. Evaluation included satisfaction surveys of patient/carers and monitoring planning for, and place of, end of life care. Excellent satisfaction scores were reported with very positive qualitative feedback. 69 patients were referred between 2010-13, with median age 83 (range 49-97 years) and high co-morbidity scores. Carer assessments enabled significant unmet supportive care needs to be addressed. Referrals to other community-based services were arranged as needed. Of the 52 patients who have died (75%), the majority (46, 88.5%) have died in community settings, with only 6 (11.5%) dying in hospital. Collaboration with renal services also facilitated transfer/community referral of other hospital patients dying with renal failure who would not previously have been identified for hospice care. Application: Increased quality of care and cost savings (from unscheduled care) have enabled on-going clinical commissioning group (CCG) funding. This accessible multi-disciplinary clinic may offer a new model of end of life care for the frail elderly, leading to CCG funding to pilot multi-disciplinary clinics for patients with other chronic diseases in partnership with the acute hospital trust.